2016
DOI: 10.5271/sjweh.3556
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of comorbid conditions to the association between diabetes and disability pensions: a population-based nationwide cohort study

Abstract: Due to high prevalence of comorbid conditions related to diabetes, prevention of permanent working capacity is important. This is the first study to explore the risk of all-cause and cause-specific disability pension among people with diabetes and compare it to that of individuals without diabetes, while taking into account the competing risks and the timing of comorbid conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Diabetes mellitus is a chronic endocrine disorder, characterized by hyperglycemia and other metabolic disorders of fat, protein and electrolytes due to absolute or relative insulin deficiency (1). Epidemiological data suggest that diabetes-induced cardiovascular complications are a leading cause of diabetes-related mortality and disability (2). Diabetes-induced cardiovascular complications include macrovascular and microvascular diseases (3), of which vascular endothelial cell apoptosis is considered to be an initial event and pathological basis (4).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a chronic endocrine disorder, characterized by hyperglycemia and other metabolic disorders of fat, protein and electrolytes due to absolute or relative insulin deficiency (1). Epidemiological data suggest that diabetes-induced cardiovascular complications are a leading cause of diabetes-related mortality and disability (2). Diabetes-induced cardiovascular complications include macrovascular and microvascular diseases (3), of which vascular endothelial cell apoptosis is considered to be an initial event and pathological basis (4).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a previous assessment found that depression, musculoskeletal problems, and multiple co-morbid conditions all increased the likelihood of receiving disability pensions. 15 Recognizing these broader consequences of diabetes on governmental finances, we sought to quantify the effects of T2D on fiscal outcomes for the Swedish government based on delays in achieving glycaemic treatment targets. 16 Building on evidence showing the impact of diabetes and related complications on work activity, a fiscal analysis was conducted that describes how efforts to reduce clinical inertia in the treatment of T2D can influence future government tax revenues and transfer payments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These complications have also been linked to an increased need for disability pensions that can increase costs for governments (but are omitted from economic evaluation because transfer payments redistribute income and wealth without directly absorbing resources or creating output). For example, a previous assessment found that depression, musculoskeletal problems, and multiple co‐morbid conditions all increased the likelihood of receiving disability pensions 15 …”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal (MS) pain is among the most common co-existing diseases among patients with T2D [3][4][5][6] and significantly associated with T2D [18][19][20][21]. MS pain has been shown to have a negative influence on activity limitations and on the odds of disability [22,23], and be negatively associated with self-care behaviours, such as physical activity levels [24] and medication adherence [25]. Moreover, people with MS pain often report psychological problems [26], which are also suggested to be associated with T2D treatment [27].…”
Section: Introductionmentioning
confidence: 99%